Does lecture attendance matter? The good, the bad and the ugly - Papageorgiou, Elmarie; Townsend, Pamela (South African Journal of Higher Education, 2016)
This article reports on a study that investigated the impact of lecture attendance on the academic performance of first-year accounting students at a South African university. The objectives of this study were, firstly, to ascertain whether lecture attendance influences students’ performance (measured in terms of their assessment scores) and, secondly, whether ‘better’ students (measured in terms of symbols obtained in English, Mathematics and Accounting in the South African National Senior Certificate) believe that lecture attendance is important in order to attain better results. The research study used a mixed method design, which was both quantitative and experimental. The findings indicate three scenarios, which are reflected in this paper as the good, the bad and the ugly, in terms of lecture attendance levels and academic performance. The value of the study resides in the insights gained about the salience of various lecture attendance trends in the first-year accounting students. Key words Academic performance, accounting students, lecture attendance, SAICA, South Africa, university